Alkaline-based curcumin extraction from selected zingiberaceae for antimicrobial and antioxidant activities - Othman, Rashidi; Abdurasid, Mohd Akram; Mahmad, Noraini; Ahmad Fadzlillah, Nurrulhidayah (Emerald Group Publishing Ltd., 2019)
Purpose – The purpose of this paper is to extract, characterise and quantify curcumin from selected Zingiberaceae of “kunyit” or turmeric (Curcuma longa), “temu lawak” or Javanese turmeric (Curcuma xanthorrhiza), “temu pauh” (Curcuma mangga), “lempoyang” (Zingiber zerumbet) and “bonglai” (Zingiber cassumunar) using alkaline and chemical-based extraction method for antimicrobial and antioxidant activities. Design/methodology/approach – Through the alkaline-based extraction method, all parts of rhizome samples were freeze-dried for 72 h before grounded into a fine powder and kept at 20°C. The powdered sample (0.1 g) was weighed and placed in a 50mL tube. About 20 mL of 2M NaOH solution was added into the tube. The solution was allowed to stand for 30 min. Then, 20 mL of ethyl acetate was added into the tube. The solution was mixed well then centrifuged at 13,500 rpm for 3 min. The upper layer was collected using a pipette. The process was repeated until the upper layer became almost colourless. The collected ethyl acetate solution was concentrated using a rotary evaporator to remove the ethyl acetate from the extracted compound. The concentrated curcumin was placed in a universal bottle, which was then dried from the remaining ethyl acetate using nitrogen drying process. The dried curcumin was then stored inside the freezer at 208C. The antimicrobial activities were using agar diffusion method against bacterial and fungi, while the antioxidant activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay. Findings – All the samples successfully showed a single peak (curcumin) that gained from the high-performance liquid chromatography (HPLC) chromatogram analysis (at 425 nm) using the alkaline-based extraction method and the highest curcumin content was in turmeric (12.9561.07mg/g DW). At 10.0 mg/mL curcumin concentration, the best antibacterial activity was against on methicillin-resistant Staphylococcus aureus (MRSA) with 7.5060.71mm inhibition zone, while the best antifungal activity was against on Aspergillus niger with 8.0060.41mm inhibition zone. The DPPH antioxidant test resulted in the highest inhibition (110.41 percent) was at 0.25mg/mL curcumin concentration. Originality/value – Through HPLC analysis, all samples successfully showed a single peak of curcumin at 425 nm. The total carotenoid determination from turmeric revealed that the content of the sample was substantially higher using alkaline-based extraction (18.4060.07 mg/g DW) compared to chemical-based extraction (9.4260.20 mg/g 6 SD).